Introduction: A family systems approach to promote maternal, child and adolescent nutrition - Judi Aubel; Stephanie L. Martin; Kenda Cunningham (Wiley, 2021)
Abstract In all cultures, women and children are embedded in family systems that determine roles, relationships, patterns of communication and authority between family members. Especially in non‐western societies, maternal and child nutrition practices are determined not only by the biological parents but also by other influential family members. Most maternal and child nutrition research and interventions do not consider the constellation of family roles and influence on women and children and continue to focus on the mother-child dyad and individual knowledge, attitudes and practices. There is growing agreement on the need to adopt an ecological framework to address public health issues, including those dealing with maternal and child nutrition. This special issue presents examples of research from a variety of settings that employed an ecological, family systems approach either to investigate maternal, child or adolescent nutrition issues or to design interventions that engaged various actors within family settings. These 11 articles contribute to a growing body of evidence supporting the relevance of a wider family systems perspective for nutrition research and interventions. Key themes across studies include the limitations of using a nuclear family model for research and intervention design, the need for formative research that comprehensively explores family systems, increasing recognition of the extensive involvement and support provided by grandmothers, and the importance of engaging men in culturally appropriate ways based on community dialogue and women's perspectives. Future maternal and child nutrition research and interventions can be strengthened by systems thinking that acknowledges that individuals are situated within family and community systems.